2013
DOI: 10.5039/agraria.v8i4a3495
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade do solo na qualidade fisiológica de sementes de soja

Abstract: RESUMOO objetivo deste trabalho foi estudar, através de ferramentas da agricultura de precisão, a variabilidade da fertilidade do solo em campos de produção de sementes de soja e o efeito na qualidade fisiológica das sementes produzidas. Inicialmente, foi estabelecido um grid de amostragem de 1 ponto por hectare onde foram realizadas as coletas de amostras de solo e de sementes. No solo foram determinados teores de fósforo (P), potássio (K), cálcio (Ca), magnésio (Mg), matéria orgânica (%), argila (%), saturaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 11 publications
2
5
0
2
Order By: Relevance
“…In the studied field, although precision agriculture tools were adopted, including georeferenced soil sampling and variablerate fertilizer application, the HY was characterized by higher OM contents, P contents and CEC in all layers evaluated, compared with LY (Table 1). Mondo et al (2012) and Mattioni et al (2013) observed positive relationship between seed PQ and soil fertility. According to Panozzo et al (2009), plants originated from high-vigor seeds produce 17% more pods in comparison to those originated from low-vigor seeds.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In the studied field, although precision agriculture tools were adopted, including georeferenced soil sampling and variablerate fertilizer application, the HY was characterized by higher OM contents, P contents and CEC in all layers evaluated, compared with LY (Table 1). Mondo et al (2012) and Mattioni et al (2013) observed positive relationship between seed PQ and soil fertility. According to Panozzo et al (2009), plants originated from high-vigor seeds produce 17% more pods in comparison to those originated from low-vigor seeds.…”
Section: Resultsmentioning
confidence: 92%
“…Factors related to the environment in which the crop grows (low or high yield potential) and plant arrangement, such as plant density (PD), can also determine seed PQ (Vazquez et al, 2008;Mondo et al, 2012). In a soybean seed production field, Mattioni et al (2011Mattioni et al ( , 2013 and Gazolla Neto et al (2015) reported the presence of spatial variability in the vigor index. Similarly, studies have concluded that the organic matter content (Mondo et al, 2012), calcium content and soil CEC effective benefited the germination index (Mattioni et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This relationship identifies regions that produce seeds with higher physiological quality and regions that produce seeds with lower physiological quality. The same phenomenon has been observed in productivity (Mattioni et al, 2011;Mondo et al, 2012;Mattioni et al, 2013;Gazolla-Neto et al, 2016). However, defined management areas for the production of seeds and technology implementation have not yet been adequately elucidated.…”
Section: Introductionmentioning
confidence: 53%
“…Indicando a heterogeneidade desses atributos na área em estudo. Vários pesquisadores (CAVALCANTE et al, 2007;DALCHIAVON et al, 2012;MATTIONI et al, 2013;GAZOLLA-NETO et al, 2015;GAZOLLA-NETO et al, 2016) também encontraram alta variabilidade espacial para o fósforo e potássio.…”
Section: Resultsunclassified